ACCULTURATION OF ISLAM AND CHRISTIAN IN BALINESE CULTURE: A HISTORICAL AND SOSIOLOGICAL STUDY - Cakranegara, Joshua Jolly Sucanta; Nadira Salsabila (Harmoni, 2024)
Abstract This study aimed to explore the comparative acculturation of Islam and Christianity, both Catholic and Protestant, within Balinese culture throughout Bali's history. Employing a qualitative descriptive method with a historical approach, this research conducted a thorough literature review encompassing history, religion, and culture. Data were gathered from historical sources and pertinent literature, with comparative analysis utilized to scrutinize these materials. The findings uncovered that the Balinese community, characterized by both closed and open cultural traits, embraced the arrival of Islam and Christianity in a harmonious manner. Both religions successfully assimilated into Balinese culture, predominantly shaped by Hindu teachings. Since Islam's introduction in the 15th century and Christianity's in the 20th century, diverse forms of acculturation have emerged, particularly evident in places of worship like mosques and churches. Despite initial resistance from rulers and the community, the acculturation process persisted. The study concluded that the integration of Islam and Christianity significantly influenced the contemporary image of Balinese culture, illustrating a continuous acculturation process throughout Bali's history. Abstrak Penelitian ini bertujuan untuk mengeksplorasi akulturasi perbandingan Islam dan Kristen, baik Katolik maupun Protestan, dalam budaya Bali sepanjang sejarah Bali. Menggunakan metode deskriptif kualitatif dengan pendekatan historis, penelitian ini melakukan tinjauan literatur yang komprehensif meliputi sejarah, agama, dan budaya. Data dikumpulkan dari sumber-sumber sejarah dan literatur terkait, dengan analisis komparatif digunakan untuk mengkaji materi tersebut. Temuan menunjukkan bahwa komunitas Bali, yang ditandai dengan karakteristik budaya tertutup dan terbuka, menerima kedatangan Islam dan Kristen secara harmonis. Kedua agama berhasil beradaptasi dalam budaya Bali yang sebagian besar dipengaruhi oleh ajaran Hindu. Sejak kedatangan Islam pada abad ke-15 dan Kristen pada abad ke-20, berbagai bentuk akulturasi telah muncul, terutama terlihat dalam tempat-tempat ibadah seperti masjid dan gereja. Meskipun menghadapi resistensi awal dari penguasa dan masyarakat, proses akulturasi tetap berlanjut. Studi ini menyimpulkan bahwa integrasi Islam dan Kristen secara signifikan memengaruhi citra budaya Bali kontemporer, menggambarkan proses akulturasi yang berkelanjutan sepanjang sejarah Bali.